Significance of Gold in Indian culture - Kakkar, Shalini; Chitrao, Dr. Pradnya V. (The journal of contemporary issues in business and government, 2023)
Gold has found a place in Indian hearts that goes of its deep-rooted significance in Indian history. Gold is considered auspicious in the Indian diaspora as it holds sentiments of bringing good fortune and destiny into their lives. It represents power and status in society. Some Indian festivals are celebrated by purchasing gold with the belief of bringing prosperity. Gold ornaments are passed on from one generation to the next as a legacy. Gold jewelry represents the journey of Indian women blending with culture in various stages of life. It is the distinctive cultural individuality that has triggered the scope of gold in people's traditions. This study examines the orientation of consumers toward ornamental gold highly influenced by cultural needs. It also analyses to find out the critical importance of gold jewelry in preserving Indian cultural heritage. The study covers both primary investigation and secondary literature review. Data is collected with the help of a structured questionnaire and is analyzed to identify the extent of consumers’ orientation for ornamental gold due to the driving force of culture.